Electrodeposition of redox active nickel-manganese metal organic framework and manganese sulfide composite for supercapacitors - Khan, Muhammad Waqas; Khan, Amir Sohail; Rohma; Pai, Shri Hari S.; Mohapatra, Gourab; Kumar, Ashish; Ali, Rana Basit; Sial, Qadeer Akbar; Seo, Hyungtak (Electrochimica Acta, 2025)
The intermittent nature of renewable energy sources and the escalating demand of energy requires the development of advanced energy storage systems. Investigation of novel energy materials are of paramount significance in the context of energy storage devices and evaluating their synthesis techniques holds equal significance. Herein, due to the fascinating features such as high surface area and porosity that the metal-organic frameworks (MOFs) hold, we have electro-synthesized nickel-manganese terephthalic acid MOF (NMT MOF) onto nickel foam substrate. To further enhance the electrochemical performance of the synthesized MOF in terms of capacity, we electrodeposited manganese sulphide onto the MOF's structure to induce synergism that boosts the overall charge storage. The synthesized samples are well characterized via structural, morphological, elemental, and electrochemical analyzations. To elucidate the electrode material from practical application point of view, we fabricated a symmetric supercapacitor that showcases decent energy and power density (34 Wh kg-1 and 4250 W kg-1) with excellent stability. Furthermore, semiempirical models are implied to attain innate understanding of the charge storage mechanics of the NiMnT-MOF/MnS electrode material.
Keywords: Battery; Charge storage; Electrode material; Energy; Manganese sulphide; Metalorganic frameworks (MOFs); Redox-active; Renewable energy source; Storage systems; Synthesised; Battery; Energy storage; MOF; Supercapacitor; Transition metals